(untitled) (Journal of Enam Medical College, 2019)
Background: Although endoscopic retrograde cholangiopancreatography (ERCP) was first described as a diagnostic technique, now-a-days we mainly do ERCP with a therapeutic intent for management of various biliary and pancreatic diseases. Objectives: This study intends to find out the diagnosis obtained by ERCP procedure and the therapeutic interventions done for appropriate cases in a tertiary level hospital in Bangladesh. Materials and Methods: This prospective observational study was performed in the Department of Gastroenterology in Enam Medical College & Hospital over a period from June 2014 to October 2016. Eighty patients, aged 15–70 years, were selected only for therapeutic ERCP. They were diagnosed and selected after taking history, physical examination and appropriate investigations. ERCP was done under short-term general anesthesia or deep sedation by using propofol or fentanyl. Results are shown in tables. Results: Majority of the cases were choledocholithiasis (53.75%) followed by cholangiocarcinoma (11.25%), ampullary carcinoma (8.75%), carcinoma of the gall bladder (6.25%), biliary ascariasis (6.25%), biliary stricture (5%), papillary stenosis (5%), chronic pancreatitis (2.5%) and sludge in the CBD (1.25%). Types of therapeutic intervention depended on diagnosis. Papillotomy with stone removal was done in patients with choledocholithiasis. Papillotomy with stenting was done in the patients with cholangiocarcinoma, ampullary carcinoma, gall bladder carcinoma, biliary stricture and paillary stenosis. Papillotomy with worm extraction was done in cases of biliary ascariasis. Papillotomy with clearing of sludge was done for sludge in the CBD and only papillotomy was done in two patients of chronic pancreatitis. Conclusion: In this study we found that choledocholithiasis and biliary tract malignancy were the two major ERCP findings. Therapeutic interventions were done according to diagnosis. The most common therapeutic intervention was papillotomy with stone removal. Next common intervention was papillotomy with stenting. J Enam Med Col 2019; 9(1): 9-15